Indium and aluminium-doped ZnO thin films deposited onto FTO substrates: nanostructure, optical, photoluminescence and electrical properties - Benhaliliba, M.; Benouis, C. E.; Aida, M. S.; Yakuphanoğlu, Fahrettin; Sanchez Juarez, A. (Springer, 2010)
The microstructure, optical, photoluminescence and electrical properties of ZnO based films deposited onto FTO glass substrates by ultrasonic spray pyrolysis have been investigated. For comparison and a better understanding of physical properties of indium- and aluminum-doped ZnO and undoped ZnO thin films, X-ray diffraction analysis, photoluminescence spectra, optical, SEM texture and electrical conductivity analyses were performed. The AZO and IZO films exhibit the nanofiber structure with diameters 260 and 400 nm. X-ray diffraction showed all samples to be polycrystalline with hexagonal ZnO. The optical band gaps of the films were varied by Al and In dopants. The photoluminescence spectra of the films show a weak broad in the visible range and shifted to green emission for indium doping and to the green blue emission for aluminum as dopant. The width of the PL spectra for aluminum-doped films is too large compared to those of the indium-doped ones. The electrical conductivity of the ZnO film changes with Al and In dopants. The position of donor levels changes with In and Al dopants and approaches the conduction band level with the metal dopants. The obtained results suggest that the metal doping has a clear effect upon the growth, optical, photoluminescence and electrical conductivity properties of the ZnO films.
Keywords: Zinc oxide; FTO; Photoluminescence; Optical; Structural and electrical properties